Scalable Cu/Cu2O-CuO/CuI heterojunction platform realizing an extended charge carrier separation suitable for photoreduction and photodegradation. Issue 6 (December 2021) - Uthirakumar, Periyayya; Devendiran, M.; Van Dao, Dung; Son, Hoki; Cho, Yeong Hoon; Lee, In-Hwan
Abstract: Degree of toxic pollutants releasing from industries create a serious environment hazardous owing to an inevitable water contamination. The design and development of innovative efficient photocatalysts are highly desirable. Herein, a facile and cost-effective method is utilized to fabricate a scalable Cu/Cu2 O-CuO/CuI heterojunction platform using an inexpensive iodine sublimation followed by post annealing process. The structural, optical, and electronic properties of the Cu/Cu2 O-CuO/CuI heterojunction are systematically investigated to realize an extended charge carrier transfer responsible for high performance in photoreduction and photodegradation. For instance, the photoreduction of 4-nitrophenol is accomplished within 1 min, under UV light irradiation. Similarly, the scalability of the proposed sheet benefits to increase the photodegradation speed of toxic dyes. Indeed, a single sheet with an active area of 4 × 4 cm 2 size Cu/Cu2 O-CuO/CuI sheet requires 6 h to degrade 95% of methylene blue dye and it requires just 30 min in case of eight sheets or with an active area of 32 × 32 cm 2 sheet. Besides, a stable recyclability with an excellent photocatalytic activity is accountable owing to the co-existence of metallic Cu, Cu2 O, CuO and CuI phases. A plausible mechanism is proposed based on the bandgap of individual phases to clarify the photoexcited charge carriers transfers at the heterojunction interface to extend the charge carrier separation. Based on the scavenger tests, it is found that the photogenerated holes and hydroxyl radicals are the main active species responsible for photodegradation of toxic dyes. Thus, the versatility in handling of scalable sheets with a stable recycle performance can be appropriate to replace the existing powder-based photocatalysts with an expensive recovery process. Graphical Abstract: ga1 Highlights: A simple method is developed to fabricate scalable Cu/Cu2 O-CuO/CuI sheet. Post-annealing process facilitates to incorporate an additional CuO phase. Enhanced photoreduction of 4-nitrophenol was accomplished within 1 min of UV light. Excellent photodegradation was realized due to an extended electron transfer. The versatility of scalable sheet replaces the conventional photocatalysts.